The Influence of Family Environment on Students' Academic Achievement at Al Ihsan Islamic Boarding School - Tarsono, Tarsono; Kurnia, Nia; Hamidah, Siti; Mubarok, Y. Zaki (CV. Strata Persada Academia, 2025)
This study investigates the influence of the family environment on students' academic achievement at Pondok Pesantren Al Ihsan. Academic achievement is shaped by various factors, both internal and external. While motivation and interest are key internal drivers, the family environment plays a significant role in academic success. The research employs a quantitative approach with a correlational method, focusing on 45 students from the 2023 KIP-K scholarship cohort. Data were collected using a Likert-scale questionnaire on family environment factors and students' GPA as a measure of academic achievement. Analysis revealed a moderate positive correlation (r = 0.535) between the family environment and students' academic achievement, with the family environment contributing 28.6% to academic performance. The findings highlight the importance of family support in fostering motivation, discipline, and learning enthusiasm, all of which are essential for academic success. This study underscores the need for collaboration between families, educators, and students to create a conducive learning environment. The research contributes to understanding the role of the family in Islamic boarding school contexts and offers practical recommendations for enhancing students' academic achievements.